Three-dimensional classical and quantum stable structures of dissipative systems - Carlo, Gabriel Gustavo (2019)
We study the properties of classical and quantum stable structures in a three-dimensional (3D) parameter space corresponding to the dissipative kicked top. This is a model system in quantum and classical chaos that gives a starting point for many body examples. We are able to identify the influence of these structures in the spectra and eigenstates of the corresponding (super)operators. This provides a complementary view with respect to the typical two-dimensional parameter space systems found in the literature. Many properties of the eigenstates, like its localization behavior, can be generalized to this higher-dimensional parameter space and spherical phase space topology. Moreover, we find a 3D phenomenon - generalizable to more dimensions - that we call the coalescence-separation of (q)ISSs, whose main consequence is a marked enhancement of quantum localization. This could be of relevance for systems that have attracted a lot of attention very recently.